Chinese Visceral Adiposity Index Is More Closely Associated With Hypertension and Prehypertension Than Traditional Adiposity Indices in Chinese Population: Results From the REACTION Study - Binqi Li; Binqi Li; Jie Wang; Xin Zhou; Xin Zhou; Xin Zhou; Yang Liu; Yang Liu; Weiqing Wang; Zhengnan Gao; Xulei Tang; Li Yan; et al. (Frontiers in Endocrinology, 2022)
PurposeThe optimal adiposity index that is strongly associated with hypertension or prehypertension remains inconclusive in Chinese population. This study aimed to investigate the relationship between Chinese visceral adiposity index (CVAI) and hypertension and prehypertension, as well as to compare the discriminative power of CVAI, visceral adiposity index (VAI), body mass index (BMI), waist circumference (WC), waist to height ratio (WHtR), low-density lipoprotein cholesterol (LDL-C), and waist-to-hip ratio (WHR) with hypertension and prehypertension in Chinese general population.Patients and MethodsA total of 34732 participants from REACTION study were recruited. Multiple logistic regression analyses were performed to detect the association between adiposity indices (CVAI, VAI, BMI, WC, WHtR, WHR, LDL-C) and hypertension and prehypertension.ResultsMultivariate logistic regression analysis showed that compared with other obesity indices, CVAI remained significantly associated with hypertension and prehypertension (Hypertension: odds ratio (OR) 3.475, 95% confidence interval (CI) 3.158-3.824, p<0.001 in total subjects; OR 2.762, 95% CI 2.369–3.221, p<0.001 in men; OR 3.935, 95% CI 3.465–4.469, p<0.001 in women, Prehypertension: OR 2.747, 95% CI 2.460-3.068, p<0.001 in total subjects; OR 2.605, 95% CI 2.176–3.119, p<0.001 in men; OR 2.854, 95% CI 2.465–3.304, p<0.001 in women).In a stratified analysis, CVAI was significantly associated with hypertension and prehypertension at any level of blood glucose, age or estimated glomerular filtration rate(eGFR).ConclusionCVAI is significantly associated with hypertension and prehypertension. CVAI shows the superior discriminative ability for hypertension and prehypertension compared with VAI, BMI, WC, WHtR, WHR and LDL-C in Chinese general population.